KARAKTERISTIK DEMAM BERDARAH DENGUE PADA ANAK DI RUMAH SAKIT UMUM ROYAL PRIMA MEDAN - Fioni Fioni (Universitas Prima Indonesia, 2020)
Dengue disease is caused by dengue virus from Arbovirus B group, that is arthropod-bone virus or virus spread by arthropod. This virus belongs to the genus Flavivirus of the Flaviviridae family. The type of research used is case study design research, descriptive with retrospective approach. The required sample size is 100 patient medical record data. The results of the study were aged 15-19 (29%), based on the most sexes were men (59%), based on the patient's main complaint were all high fever (100%), based on the additional complaints most were nausea + vomiting + rash + headache + (23%), based on most inspection was the rash (40%), based on the patient's palpation were all soepel (100%), based on percussion of patients all were tympanic (100%), based on the most frequent tourniquet test is Positive (56%), based on the most common hemoglobin examination (89%), based on the most common hematocrit examination (89%), , based on the most frequent leukocyte examination is abnormal (89%), based on platelet based patients all are thrombocytopenia (100%).